2014
DOI: 10.1007/s13201-014-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality for irrigation: a case study from Bandalamottu lead mining area, Guntur District, Andhra Pradesh, South India

Abstract: Quality of water resources in the Bandalamottu area of Guntur District of Andhra Pradesh in South India is facing a serious challenge due to Pb mining. Therefore, 40 groundwater samples were collected from this area to assess their hydrogeochemistry and suitability for irrigation purposes. The groundwater samples were analyzed for distribution of chemical elements Ca 2? , Mg 2? , Na ? , K ? , HCO 3-, CO 3 2-, F-, Cl-, and SO 4 2-. It also includes pH, electrical conductivity, total hardness, non-carbonate hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 24 publications
(18 reference statements)
0
72
0
Order By: Relevance
“…Moreover, Frenkel (1984) has concluded that arid and semi-arid regions of surface and subsurface water was nearly saturated with respect to CaCO 3 , and also contains high concentrations of sulfate and calcium which could be precipitated in the soil. Visual MINTEQ (3.1) has widely been used to estimate the saturation index (SI) of the groundwater with respect to mineral phases (Gustafsson 2012; Nagaraju et al 2014;Appelo and Postma 1996). The solubility products of several minerals which Fig.…”
Section: Hydrogeochemical Saturation Index Statesmentioning
confidence: 99%
“…Moreover, Frenkel (1984) has concluded that arid and semi-arid regions of surface and subsurface water was nearly saturated with respect to CaCO 3 , and also contains high concentrations of sulfate and calcium which could be precipitated in the soil. Visual MINTEQ (3.1) has widely been used to estimate the saturation index (SI) of the groundwater with respect to mineral phases (Gustafsson 2012; Nagaraju et al 2014;Appelo and Postma 1996). The solubility products of several minerals which Fig.…”
Section: Hydrogeochemical Saturation Index Statesmentioning
confidence: 99%
“…The over dependence on groundwater for drinking, agricultural and industrial sector and different climatic and natural phenomenon causes coastal groundwater contamination (Srinivas et al 2015). Besides, different geochemical processes in groundwater governing the chemical characteristics of groundwater, is well documented in many parts of the world by many authors i.e., Montety et al (2008), Jalali (2009), Manjusree et al (2009), Thilagavathi et al (2012, Sivasubramanian et al (2013), Nagaraju et al (2014), Kumar et al (2015), Islam et al (2016a, b) and Balaji et al (2016). Geochemical studies of groundwater provide a better understanding of water quality and possible changes .…”
Section: Introductionmentioning
confidence: 99%
“…These diagrams are widely employed to assess the functional sources of dissolved chemical constituents, such as precipitation, rock, and evaporation dominance [31]. A similar study has been carried out by [11] and emphasized the mechanisms that control the chemistry of groundwater in Karnataka. The Gibbs ratios are calculated with the formulae given below:…”
Section: Gibbs Ratiomentioning
confidence: 99%
“…Mixed sources may be discovered by using factor analysis, a statistical procedure of multivariate analysis [9,10]. In this context, thermodynamic water equilibrium studies are usually made with sophisticated computer programs, such as MINTEQ [11].…”
Section: Introductionmentioning
confidence: 99%